Workshop with researchers coffee growers for the control of Beauveria bassiana over ffypothenemus hampei (Coleoptera: Scolytidae) - POSADA-F., FRANCISCO; SALAZAR-E., HUGO MAURICIO; ARISTIZÁBAL, LUIS FERNANDO; GONZALO-MEJÍA, CARLOS; JIMÉNEZ, MAURICIO (Revista Colombiana de Entomología, 2003)
Beauveria bassiana (Bb) (Balsamo) is a natural enemy of the coffee berry borer (CBB), Hypothenemus hampei (Ferrari), that causes the highest mortality. Some coffee farmers have produced, applied and observed the Bb effect in the field as a white spot on CBB adults. However, the main challenge is knowing the amount of CBB that is controlled by the fungus. The environmental moisture can encourage and constrain the fungus expression, for this reason, when evaluated, its control participation is under estimate. The objective of this study was to evaluate the natural effect of Bb in field conditions, with workshops attended by coffee growers from three "veredas": Riosucio (Caldas), Balboa y Santa Rosa de Cabal (Risaralda). Samples of coffee berries were collected at random, the position of CBB into the berry’s tunnel was illustrated and the berries were dissected. The dead and living CBBs were individually put in vials and left in a chamber under controlled humidity for 15 days. The coffee growers recorded the berry perforations, the number of living and dead CBB’s (with and without fungus), missing CBBs, and their position inside the berry. From the evaluation, the coffee growers found that the fungus Bb is present in their farms. They also recognized that the Bb was present in living and dead specimens (without any sign of disease), which showed the infection only after being left in a humidity chamber. In Riosucio the fungus was present in ali farms with a variation of 9, 1 to 55%. In Balboa it was present in three of four farms with a variation of 7,5 to 81 %. In Santa Rosa de Cabal it was present in three of five farms and the highest leve! of infection found was 6,4%.